1821–1831: Transition from pre-modernity to modern society in Greece. Issue 4 (2nd October 2022) - Veremis, Thanos Μ.
ABSTRACT: Within a decade of the Greek War of Independence, social entities, segmented by familial institutions, client-based networks, and ties of locality, began their transition to modernity. Instead of exclusive loyalty to the family and place of birth, modern identity turns to the abstraction of an 'imagined community' – that of the nation. Embracing modernity involved an expansion of cognition to accept the reality of concepts not subject to sensory verification. A variety of autobiographical works and historical memoirs will provide evidence of transition and the difficulties that its verification entails. The views of different segments of society concerning their place and role in the war were never uniform nor unchanging. This article discusses the works that produce conflicting evidence on the decade in question and subsequent times when most of the memoirs appeared in print.